1995
DOI: 10.1143/jjap.34.5567
|View full text |Cite
|
Sign up to set email alerts
|

Current-Voltage and Capacitance-Voltage Characteristics of Metal/Oxide/6H-Silicon Carbide Structure

Abstract: This study is part of a project that is aimed at building dynamic boundary conditions near a solid wall, in order to reduce the large eddy simulation spatial resolution that is necessary in this region. The objective is to build a low-order dynamical system in a plane parallel to the wall, which will mimic the unsteady behaviour of turbulence. This dynamical system should be derived from a POD decomposition of the velocity field. The POD decomposition is to be applied on an experimental database of time-resolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Additionally, the results in the Fig. 6 suggest that the difference of the linear growth rate coefficient between the a-and the m-face is negligible for low temperature regime, which is in agreement with Tokura et al 19 Fig . 7 shows that the growth rate enhancement parameter for thin oxides for all four crystallographic faces is temperature-dependent.…”
Section: Fig 5 Arrhenius Plots For Parabolic Growth Rate Coefficiensupporting
confidence: 90%
See 2 more Smart Citations
“…Additionally, the results in the Fig. 6 suggest that the difference of the linear growth rate coefficient between the a-and the m-face is negligible for low temperature regime, which is in agreement with Tokura et al 19 Fig . 7 shows that the growth rate enhancement parameter for thin oxides for all four crystallographic faces is temperature-dependent.…”
Section: Fig 5 Arrhenius Plots For Parabolic Growth Rate Coefficiensupporting
confidence: 90%
“…On the other hand, the two other orientations, C-and a-face, show conclusive results that are in line with the findings of Goto et al 3 For m-oriented SiC, there are no comparisons possible yet, as these are the first proposed parameters for dry thermal oxidation of 4H-SiC m-face. Overall, the growth rates obtained in this study show excellent results in process simulations with SILVACO's Victory Process 32 with respect to the experimental findings 19,38 (see follow-up results 44 ). Table I provides an overview of the obtained activation energies and the pre-exponential factors of Arrhenius plots for all the four inspected crystallographic faces.…”
Section: Fig 5 Arrhenius Plots For Parabolic Growth Rate Coefficiensupporting
confidence: 70%
See 1 more Smart Citation
“…The growth speed of the oxide film is faster on the (0001 _ )C surface than on the (0001)Si surface. Tokura and colleagues examined in detail the anisotropy of the thermal oxidation of 6H-SiC [17]. They concluded that the anisotropy of the oxidation rate is due to the generation of the interface oxide Si 4 C 4-x O 2 , and the oxidization rate on the Si surface is lowered by the interface oxide, which prevents oxidation.…”
Section: Oxidization Processmentioning
confidence: 99%
“…The MOS channel in UMOSFETs is formed on trench sidewalls created by RIE. Though the MOS channel properties greatly affect the total UMOSFET performance [3,4], there are few reports related to the MOSFET performance formed on the trench sidewalls. In addition to that, the different surface orientation appears at the trench sidewalls.…”
Section: Introductionmentioning
confidence: 99%